Ethical and regulatory principles of clinical trials - Hackshaw, Allan (Henry Stewart Talks, 2025)
Ensuring participant safety and well-being, Good Clinical Practice (GCP), GCP & trial participants and trial investigators, Main regulations for clinical trials, Independent ethics review and national regulatory agency review, Participant or Patient Information Sheet (PIS), Informed consent from trial participants